Removal and discharge of microplastics from the wastewater treatment plants in İstanbul - Vardar, Suat. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2020., 2020)
Wastewater treatment plants (WWTPs) act as both receivers and sources of microplastics as they both receive microplastics from household and commercial activities and release the particles that could not be retained. This study investigated several units of a tertiary WWTP with a nutrient removal unit. Samples after physical treatment and from the effluent were also taken as 3h composite samples in order to observe fluctuation effect of influent wastewaters. Dried sludge from the WWTP was also investigated for potential hazards with application of the sludge to the soils. Particles isolated from samples were divided into fibers, fragments, nylons, pellets and glitters based on their morphological characters. Fibers were the most dominant shape, followed by fragments. 500-1000 μm and 1000-2000 μm was the most common size ranges for wastewater samples and sludge, respectively. Size distributions were different for shape classes. Particles in different size ranges demonstrated distinct behaviors for some size classes in various units of the WWTP. Fragments <500 μm were removed more efficiently where fibers with sizes 250-500 μm and 1000-2000 μm were removed better within the WWTP. 84.6 and 93.0% removal were observed with grab and composite samples. Despite the high removal rates 5,151x106 particles/d were released to Marmara Sea where, 36 days of discharge was equal to abundance value reported for Marmara Sea and 5,069x106 particles/d were present in the dried sludge. Polymer structures were not confirmed therefore, the rates calculated represent the microlitter release and microplastic release rate should be lower with a characterization step utilized.
Keywords: Sewage disposal plants -- Turkey.; Microplastics -- Environmental aspects.; Water -- Pollution.